Valorization of low-cost agro-wastes residues for the maximum production of protease and lipase haloextremozymes by Haloferax lucentensis GUBF-2 MG076078. (February 2021) - Gaonkar, Sanket K.; Furtado, Irene J.
Graphical abstract: Highlights: An extracellular inducible lipase and constitutive protease haloextremozymes were simultaneously produced by Haloferax lucentensis GUBF-2 MG076078. The optimum NaCl for lipase haloextremozymes and protease production was 30 %, hence extremely halophilic. Haloferax lucentensis GUBF-2 MG076078is a multienzyme producer and used for the valorization of agro-wastes. Shrimp waste gave the highest protease, while coconut oil cake showed the highest lipase under optimal growth conditions. The partially purified lipase and protease (called HLLPase) was used as Haloextremozyme-Bio-Additive in detergent formulation. Abstract: Agro-food wastes rich in macronutrients are a replacement for expensive carbon and nitrogen sources used for enzyme production. In the present study, we aimed to valorize low-cost agro-wastes for the simultaneous production of protease and lipase haloextremozyme using Haloferax lucentensis GUBF-2 MG076078, characterization of agro-waste residues, and to apply haloextremozyme as Bio-additive in detergent formulation. It was observed that GUBF-2 efficiently hydrolyzed nine different agro-wastes with shrimp waste, and coconut oil cake yielded the highest protease (101.9 U/mL) and lipase (5.83 U/mL), respectively, under optimized conditions of 30 % NaCl, pH 6, and 42 °C. Further, SDS-PAGE of cell-free fermented agro-wastes revealed peptides from 212 to 34.6 kDa. Hydrolysates functioned as DPPH radical scavengers with maxima for shrimp waste (45.0 ± 1.15 %). SEM manifested structural alteration of fermented residues. FTIR showed degradation of proteins observed as 1640−1652 and 840−881 cm −1 absorptions with a fading peak at 1742 cm −1 indicating triacylglyceride hydrolysis. Furthermore, haloextremozyme-bio-additive detergent formulation efficiently removed 67.6 ± 3.19 % oil and 61.0 ± 3.60 % blood stains than 0.5 % Triton X-100. Conclusively, Haloferax lucentensis GUBF-2 MG076078 is a prospective strain for simultaneous protease and lipase haloextremozyme production from agro-food wastes, considering both cost efficiency and associated waste disposal problems.